Functional features in language and space : insights from perception, categorization, and development - Carlson, Laura Anne, 1965-; Zee, Emile van der (Oxford linguistics., 2005)
Notions of 'function', 'feature' and 'functional feature' are associated with relatively new developments and insights in several areas of cognition. This book brings together definitions, insights and research related to defining these notions from diverse areas, including language and perception.